An anti-mycobacterial conjugated oligoelectrolyte effective against Mycobacterium abscessus - Zhang, Kaixi (2024)
Infections caused by nontuberculous mycobacteria have increased more than 50% in the past two decades and more than doubled in the elderly population. Mycobacterium abscessus (Mab), one of the most prevalent of these rapidly growing species, is intrinsically resistant to numerous antibiotics. Current standard-of-care treatments are not satisfactory, with high failure rate and notable adverse effects. We report here a potent anti-Mab compound from the flexible molecular framework afforded by conjugated oligoelectrolytes (COEs). A screen of structurally diverse, noncytotoxic COEs identified a lead compound, COE-PNH2, which was bactericidal against replicating, nonreplicating persisters and intracellular Mab.COE-PNH2 had low propensity for resistance development, with a frequency of resistance below 1.25 × 10-9 and showed no detectable resistance upon serial passaging. Mechanism of action studies were in line with COE-PNH2 affecting the physical and functional integrity of the bacterial envelope and disrupting the mycomembrane and associated essential bioenergetic pathways. Moreover, COE-PNH2 was well-tolerated and efficacious in a mouse model of Mab lung infection. This study highlights desirable in vitro and in vivo potency and safety index of this COE structure, which represents a promising anti-mycobacterial to tackle an unmet medical need.